Cardiovascular Risk and Health Among People With Human Immunodeficiency Virus (HIV) Eligible for Primary Prevention: Insights From the REPRIEVE Trial. (16th June 2021) - Douglas, Pamela S; Umbleja, Triin; Bloomfield, Gerald S; Fichtenbaum, Carl J; Zanni, Markella V; Overton, Edgar T; Fitch, Kathleen V; Kileel, Emma M; Aberg, Judith A; Currier, Judith; Sponseller, Craig A; Melbourne, Kathleen; et al.
Abstract: Background: In addition to traditional cardiovascular (CV) risk factors, antiretroviral therapy, lifestyle, and human immunodeficiency virus (HIV)-related factors may contribute to future CV events in persons with HIV (PWH). Methods: Among participants in the global REPRIEVE randomized trial, we characterized demographics and HIV characteristics relative to ACC/AHA pooled cohort equations (PCE) for atherosclerotic CV disease predicted risk and CV health evaluated by Life's Simple 7 (LS7; includes smoking, diet, physical activity, body mass index, blood pressure, total cholesterol, and glucose). Results: Among 7382 REPRIEVE participants (31% women, 45% Black), the median PCE risk score was 4.5% (lower and upper quartiles Q1, Q3: 2.2, 7.2); 29% had a PCE score <2.5%, and 9% scored above 10%. PCE score was related closely to known CV risk factors and modestly (<1% difference in risk score) to immune function and HIV parameters. The median LS7 score was 9 (Q1, Q3: 7, 10) of a possible 14. Only 24 participants (0.3%) had 7/7 ideal components, and 36% had ≤2 ideal components; 90% had <5 ideal components. The distribution of LS7 did not vary by age or natal sex, although ideal health was more common in low sociodemographic index countries and among Asians. Poor dietary and physical activity patterns on LS7 were seen across all PCE scores, including the lowest risk categories. Conclusions: Poor CV health by LS7 was common among REPRIEVE participants, regardless of PCE. This suggests a critical and independent role for lifestyle interventions in conjunction with conventional treatment to improve CV outcomes in PWH. Clinical Trials Registration: NCT02344290. AIDS Clinical Trials Group study number: A5332. Abstract : Measures of cardiovascular (CV) risk and health are not closely related in persons with human immunodeficiency virus (HIV) in the REPRIEVE trial. Poor health scores among low-CV-risk persons with HIV suggest a critical role for lifestyle interventions regardless of CV risk prediction.